Genome sequences of two freshwater betaproteobacterial isolates, Limnohabitans species strains Rim28 and Rim47, indicate their capabilities as both photoautotrophs and ammonia oxidizers - Zeng, Yonghui; Kasalický, Vojtech; Šimek, Karel; Koblížeka, Michal (Journal of bacteriology, 2012)
Betaproteobacterial genus Limnohabitans represents an important part of freshwater bacterioplankton. Here, we report genome sequences of two Limnohabitans isolates, Rim28 and Rim47. They contain a complete photosynthesis gene cluster, RuBisCO, CO dehydrogenase, ammonia monooxygenase, and sulfur-oxidizing genes, which indicates a great metabolic versatility of the Limnohabitans species.
Keywords: Ammonia; oxidace-redukce; Molecular Sequence Data; Betaproteobacteria; Photosynthesis; molekulární sekvence - údaje; Comamonadaceae; amoniak; Oxidation-Reduction; Genome, Bacterial; fotosyntéza; genom bakteriální